2018
DOI: 10.1136/bmj.k4226
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety of immune checkpoint inhibitors in cancer: systematic review and network meta-analysis

Abstract: ObjectiveTo provide a complete toxicity profile, toxicity spectrum, and a safety ranking of immune checkpoint inhibitor (ICI) drugs for treatment of cancer.DesignSystematic review and network meta-analysis.Data sourcesElectronic databases (PubMed, Embase, Cochrane Library, and Web of Science) were systematically searched to include relevant studies published in English between January 2007 and February 2018.Review methodsOnly head-to-head phase II and III randomised controlled trials comparing any two or three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
313
2
9

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(365 citation statements)
references
References 80 publications
25
313
2
9
Order By: Relevance
“…We found that the anti-PD-1 therapy appeared to illicit greater treatment benefits compared with the anti-PD-L1 therapy, which is consistent with the previous hypothesis that NSCLC patients with anti-PD-1 therapy are more likely to experience prolonged survival and a more tolerable safety prolife than anti-PD-L1 therapy Wei et al, 2017;Xu et al, 2018). Theoretically, the interaction between PD-1 and PD-L1 as the dominant ligand, can be inhibited by both PD-L1 blockers and PD-1 blockers.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the anti-PD-1 therapy appeared to illicit greater treatment benefits compared with the anti-PD-L1 therapy, which is consistent with the previous hypothesis that NSCLC patients with anti-PD-1 therapy are more likely to experience prolonged survival and a more tolerable safety prolife than anti-PD-L1 therapy Wei et al, 2017;Xu et al, 2018). Theoretically, the interaction between PD-1 and PD-L1 as the dominant ligand, can be inhibited by both PD-L1 blockers and PD-1 blockers.…”
Section: Discussionsupporting
confidence: 89%
“…The main limitation of this study is the exclusion of immune checkpoint inhibitor drugs (e.g., nivolumab, pembrolizumab, ipilimumab, tremelimumab, atezolizumab), even though these drugs are now being positioned as first‐line therapy in combination with standard‐of‐care therapies. Recently, some researchers discussed the toxicity profiles of immune checkpoint inhibitors . Although it is difficult to compare the results between these investigations and our study, findings from this paper should contribute to a deeper understanding of the complete picture of the toxicity profiles for CD, MTA, IMD, and CV, and are consequently expected to be useful for the identification, assessment, and management of toxicities related to these drugs.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, some researchers discussed the toxicity profiles of immune checkpoint inhibitors. [26][27][28] Although it is difficult to compare the results between these investigations and our study, findings from this paper should contribute to a deeper understanding of the complete picture of the toxicity profiles for CD, MTA, IMD, and CV, and are consequently expected to be useful for the identification, assessment, and management of toxicities related to these drugs. In addition, the cancer types of the patients enrolled into early-phase trials were heterogenous; however, note that patients with solid and hematologic cancers were included in our analyses when interpreting the results of this study.…”
Section: Discussionmentioning
confidence: 75%
“…Traditional chemotherapeutic drugs work by killing rapidly dividing cells, whether they are tumor or healthy. Due to the long-term clinical application, the toxicities of chemotherapy drugs that reduce the quality of life of patients have been clearly demonstrated [47]. In the era of precision medicine, it is proposed that the treatment should not only cure diseases, but also restore patients' health with the maximum quality of life [48].…”
Section: Discussionmentioning
confidence: 99%